Perlindungan Hukum Debitur Melalui Gugatan Perdata atas Lelang Sewenang-Wenang oleh Kreditur dalam Perjanjian Hak Tanggungan - Yoga Pratama, Ari; Indra Muhtar, Muhammad; Dian Asha, Wafiyatun; Dwi Jayanti, Kharin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Indonesia is a legal state, a legal state is a state that carries out all its rights and obligations in accordance with the constitution. It is stated in article 28D paragraph 1 which states that "Everyone has the right to recognition, guarantees, protection and fair legal certainty as well as equal treatment before the public". The purpose of this research is to find out the legal provisions for implementing mortgage rights auctions on land and legal protection for debtors resulting from auctions of collateral objects with procedural defects in mortgage rights agreements. The research method has meaning, namely regarding how to conduct research. Regarding this theme, we use the Normative Juridical research method, which is a type of carrying out legal research that uses the main materials for preparation, namely books on principles, journals, doctrine, legal rules and legislation for research. Legal provisions regarding auctions have been regulated in UUHT article 6 and the protection effort that can be taken by the debtor is to file a lawsuit against the law.